Local knowledge of the Sundanese community on traditional foods to enhance the family food security - Iskandar, Budiawati Supangkat; Iskandar, Johan; Mulyanto, Dede; Aliifah , Felicia (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
Sundanese people in rural West Java have a rich the local knowledge on a variety of traditional foods. However, studies on the local knowledge of Sundanese rural communities on the variety of traditional foods are still rare. The objective of this article is to elucidate the local knowledge of Cijambu Village community, Tanjungsari Sub-district, Sumedang District, West Java, on the traditional foods. The method used in this study was qualitative with Gastronomic Ethnobiological approach. It may be defined as the study of the complex interactions between human societies, food, and their environment. The result of study showed that there are at least 26 types of traditional foods that are usually created by the local community of Cijambu Village. The producing of a variety of traditional foods is based on local knowledge of the rural people as a result of inheritance from one generation to another. The basic ingredients for creating a variety of traditional foods are mainly used various plants that are produced from village agroecosystem. At least 39 species of plants representing 21 families are predominantly used to create 26 types of traditional food of Cijambu village community. Almost all of those plants are obtained from the production of various village agroecosystems of Cijambu, including homegarden, upland field, and wet-rice fields. The existence of a variety of traditional foods in rural areas, in addition to maintaining the identity of the village traditional food cultures, is also important to support food security in rural areas.